2018
DOI: 10.3389/fimmu.2018.01107
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong Impacts of Moderate Prenatal Alcohol Exposure on Neuroimmune Function

Abstract: In utero alcohol exposure is emerging as a major risk factor for lifelong aberrant neuroimmune function. Fetal alcohol spectrum disorder encompasses a range of behavioral and physiological sequelae that may occur throughout life and includes cognitive developmental disabilities as well as disease susceptibility related to aberrant immune and neuroimmune actions. Emerging data from clinical studies and findings from animal models support that very low to moderate levels of fetal alcohol exposure may reprogram t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 117 publications
0
20
1
Order By: Relevance
“…Taken together, the results of numerous studies indicate that neuroimmune signaling plays a key role in the development of alcohol-related brain disorders. Chronic ethanol sensitizes both systemic and brain responses to the neuroimmune-gene, resulting in the hypothalamic-pituitary-adrenal (HPA)-mediated enhancement of peripheral cytokines, which further exacerbates the neuroimmune response, which increases neurodegeneration [87][88][89][90]. In addition to neuroimmune signaling, glutamate excitotoxicity also is linked to alcoholic neurodegeneration.…”
Section: High Wine Consumptionmentioning
confidence: 99%
“…Taken together, the results of numerous studies indicate that neuroimmune signaling plays a key role in the development of alcohol-related brain disorders. Chronic ethanol sensitizes both systemic and brain responses to the neuroimmune-gene, resulting in the hypothalamic-pituitary-adrenal (HPA)-mediated enhancement of peripheral cytokines, which further exacerbates the neuroimmune response, which increases neurodegeneration [87][88][89][90]. In addition to neuroimmune signaling, glutamate excitotoxicity also is linked to alcoholic neurodegeneration.…”
Section: High Wine Consumptionmentioning
confidence: 99%
“…However, it is also important to consider that although infection outcomes were not documented, previous research has suggested that low levels of PAE may underlie susceptibility to the development of autoimmune diseases through dysregulated cytokine production . Notably, preclinical research has demonstrated that both peripheral and central cytokines as well as C‐reactive protein (CRP), a marker of inflammation, were altered in female rat offspring with PAE.…”
Section: Discussionmentioning
confidence: 99%
“…18 These studies were conducted in children of different ethnicities, and consequently, this is an area that requires further research in However, it is also important to consider that although infection outcomes were not documented, previous research has suggested that low levels of PAE may underlie susceptibility to the development of autoimmune diseases through dysregulated cytokine production. 44 Notably, preclinical research has demonstrated that both peripheral and central cytokines 8 as well as C-reactive protein (CRP), 39 a marker of inflammation, were altered in female rat offspring with PAE. Specifically, animals showed increased pro-inflammatory cytokines in serum, hippocampus, and prefrontal cortex and decreased levels in the spleen and hypothalamus 8 and increased serum CRP.…”
Section: Studies Assessing Infection Outcomesmentioning
confidence: 99%
“…Taken together, the results of numerous studies indicate that neuroimmune signaling play a key role in the development of alcohol-related brain disorders. Chronic ethanol sensitizes both systemic and brain responses to neuroimmune-gene resulting in the hypothalamic-pituitaryadrenal-(HPA)-mediated enhancement of peripheral cytokines, which further exacerbates the neuroimmune response which increases neurodegeneration [67][68][69][70]. In addition to neuroimmune signaling, glutamate excitotoxicity also is linked to alcoholic neurodegeneration.…”
Section: High Wine Consumptionmentioning
confidence: 99%